Review of Small Cell Carcinomas of the Prostate - P. Furtado; M. V. A. Lima; C. Nogueira; M. Franco; F. Tavora (Prostate Cancer)
Small cell carcinoma of the prostate is a rare neoplasm, with only a few series hitherto reported. A little less than half of the cases are associated with conventional acinar adenocarcinoma, which are usually high grade. Although consensus has not been reached, the majority of patients with small cell neuroendocrine carcinoma of the prostate have advanced disease at diagnosis and disproportionally low PSA levels compared to patients with conventional acinar adenocarcinoma. Treatment consists mainly of chemotherapy associated with surgery. Radiation therapy is reserved for selected cases. This study reviews the most up-to-date information on small cell carcinomas of the prostate.